Forms of Social Capital on Halal Tourism in Bandung - Moh. Dulkiah (GoAcademica Research & Publishing, 2020)
This article focuses on the social capital of local communities in the development of halal tourism. This article aims to understand the social capital of local communities in their efforts to develop halal tourism in Bandung, West Java. The paradigm approach used is qualitative with the method of extracting data in-depth interviews and documentation review methods. This research found that the potential of local communities in the development of halal tourism lies in the trust and values ​​that develop in the community. Trust is focused on the emergence of expectations from the community towards the management of sharia-based tourism objects. While values ​​are inherent in positive local virtues in tourism development. This study concludes that halal tourism correlates with the expectations and values ​​that develop in local communities.